Current Status of Computed Tomography in Novel Coronavirus Disease 2019 Pneumonia - Kumble Seetharama Madhusudhan; Deep Narayan Srivastava (Annals of the National Academy of Medical Sciences (India), 2020)
The novel coronavirus disease, known as severe acute respiratory syndrome coronavirus 2 (SARS-CoV2), has developed into a pandemic affecting more than three million people worldwide. It predominantly affects the respiratory system and patients present with fever, dry cough, dyspnea, and myalgia. The confirmatory diagnostic test is real-time reverse transcriptase polymerase chain reaction on blood or respiratory samples. Imaging with computed tomography, although not routinely recommended, may not only assist in making a diagnosis but also in assessing disease progression, assessing complications, and in prognostication. This review describes the objectives, techniques, imaging features, and reporting of computed tomography findings of SARS-CoV2 pneumonia.